Quality of cervical screening in the well woman clinics in Kalutara District - D. T. P. Liyanage; R. de A. Seneviratne (College of Community Physicians of Sri Lanka, 2005)
Introduction The objective of this study was to assess the quality of cervical screening services in Well Woman clinics in the Kalutara District   Methodology A cross sectional survey of service prov1s1on, availability of physical facilities, performance of clinic activities including cervical screening in Well Woman clinics (WWC) and quality of follow up of clients in the clinics and field was carried out. A scoring system was developed for assessing quality and a consensus standard of quality was set by a panel of experts.   Results All clinics (l 00%) performed Pap smear testing, but only three of the seven clinics conducted four or more clinic sessions a month per DDHS area as recommended in the guidelines sent by the Ministry of Health.   The percentage mean scores of quality were: availability of required physical facilities in the WWCs - 73%; performance of general activities - 70%; cervical screening procedures 39.8%. Consensus by experts on expected percentage for above indicators of quality was >90%. The mean duration between Pap test and receiving the report was 3.4 ± 2.25 months. Four (9%) clients with abnormal reports were lost to further care.  Only one (1)  referral from the WWCs to gynaecology clinics, of 162 referrals were referred back to WWC from the gynaecology clinics.   Conclusions Facilities and service provision in the WWCs need improvement. Follow up care has to be strengthened by issuing guidelines to staff working in WWCs and referral clinics in secondary care institutions. Staff in referral institutions needs to be oriented to provide care of referred patients. Delay of reporting on Pap smears has to be rectified.